KECERDASAN EKOLOGIS DALAM BUKU SEKOLAH ELEKTRONIK MATA PELAJARAN BAHASA INDONESIA SMP - Suwandi, Sarwiji; Yunus, Ahmad; R, Laili Etika (LITERA, 2016)
This study aims to explain ecological intelligence contents in electronic Indonesian language course books for junior high school (JHS) students. The methods in the study were literature review and content analysis. The ecological intelligence contents in the books include: (1) identifying ecosystem components; (2) comprehending the functions and uses of the components; (3) understanding environmental management systems; (4) understanding environmental values which comprise local wisdom and religious and normative values; (5) showing concern about environmental destruction and pollution; (6) adapting behavior to the environment; (7) solving problems arising from environmental impacts, either individually or collectively; (8) managing/preserving natural resources; and (9) exploiting the environment positively. The ecological intelligence contents are still dominated by the cognitive aspect and have not emphasized the comprehension, value internalization, and application aspects.